(untitled) (Scientific journal of the Fergana State University, 2022)
The article extensively analyzes the artistic-aesthetic and educational-educational aspects and peculiarities of Abdulla Avloni’s stories for children. Contributions to the development of Uzbek children’s storytelling are highlighted.Also, some of A. Avloni’s stories were analyzed in comparison with Aesop’s stories. Attention was paid to the influence of third-person aspects on the author’s style in the stories aimed at highlighting the image of children and their activities, and eliminating some of the wrong habits encountered in them.